ANALISIS KANDUNGAN FORMALIN PADA BAKSO TUSUK YANG BEREDAR DI BEBERAPA SEKOLAH DASAR DI KOTA MANADO - Muhatir, Ary; Sudewi, Sri; Rotinsulu, Henki (PHARMACON, 2019)
ABSTRACT Formalin is a solution which made from 37% formaldehyde in water which is commonly used as preservative for cosmetic products and various types of non-food industrial materials. The use of formalin as a preservative in food is very dangerous for health. The purpose of this study was to determine the presence of formalin found in skewered meatballs circulating in several elementary schools in the city of Manado. Sampling was done in Malalayang Elementary School (A), State Elementary School 6 Manado (B), State Elementary School 9 Manado (C) and State Elementary School 29 Manado (D). In a qualitative test, Nash reagents were used to determine the presence of formalin in the sample. Nash reagent was used to indicate the presence of Formalin content in a sample marked with a change in color to yellow. The results of this study showed that twelve samples of skewers from four elementary schools in Manado City did not contain formalin or safe from formalin use.   Keywords: Formalin, Formaldehyde, Skewered Meatballs, Nash Reagent, Qualitative Analysis  ABSTRAK Formalin merupakan larutan yang dibuat dari 37% formaldehida dalam air yang umumnya digunakan sebagai bahan pengawet produk kosmetik dan berbagai jenis bahan industri non makanan. Penggunaan formalin sebagai bahan pengawet pada makanan sangat berbahaya bagi kesehatan. Tujuan penelitian ini yaitu untuk mengetahui keberadaan formalin yang terdapat pada bakso tusuk yang beredar di beberapa Sekolah Dasar di Kota Manado. Pengambilan sampel dilakukan di SD Negeri Malalayang (A), SD Negeri 6 Manado (B), SD Negeri 9 Manado (C) dan SD Negeri 29 Manado (D).  Pada pengujian kualitatif digunakan pereaksi Nash untuk mengetahui adanya formalin pada sampel. Pereaksi Nash ini digunakan untuk menunjukkan adanya kandungan Formalin pada sampel yang ditandai dengan perubahan warna menjadi kuning. Hasil penelitian ini menunjukkan bahwa dua belas sampel bakso tusuk dari empat Sekolah Dasar di Kota Manado tidak mengandung formalin atau aman dari penggunaan formalin. Kata Kunci: Formalin, Formaldehida, Bakso Tusuk, Pereaksi Nash, Analisis Kualitatif